Sesquiterpene Lactone and Triterpene from Pulicaria laciniata - Aberkane, M.C.; Dibi, A.; Khettache, M.; Mosset, P.; Bouakkar, L. (Asian Journal of Chemistry, 2010)
In the present note, an investigation on aerial parts of Pulicaria laciniata has been done. Two new compounds 10α,14H-i-epi univiscolide (1) and 3β-O-acyl lupeol ester (2) have been identified.